The gender wage gap: exploring the explanations - Andersen, Jaime (Kansas State University, 2008)
This paper examines some common explanations for the earnings gap between males and females. Over recent decades, the average pay of women has increased faster than the average pay of men; however, a substantial earnings gap remains. As of 2006, the U.S. Census estimated that for year-round full-time workers the earnings ratio of women to men was 77%; in other words, for every one dollar a man earns, a woman earns $0.77. The wage gap likely consists of both non-discriminatory and discriminatory aspects, and concern remains over how much of the gender wage gap is caused by discrimination against women. However, the part of the wage gap due to discrimination cannot be measured directly, so it is typically interpreted as the portion of the gap that is "unexplained" by other factors. Numerous economists and sociologists have studied this issue, but their conclusions differ vastly. This paper discusses various economic explanations for the gender pay gap, both discriminatory and non-discriminatory. It also briefly summarizes some sociological responses to economic arguments, as well as some policy recommendations and their possible implications.
Keywords: Wage; Discrimination; Gender; Pay gap; Explanations; Earnings ratio; Economics, Labor (0510)